Dollarization as an effective commitment device: The case of Argentina - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
One of the main reasons to dollarize an emerging market economy is to eliminate high, persistent, and volatile inflation. To be effective, dollarization must generate sufficient credibility, which in turn depends critically on whether its expected probability of reversal is low. Argentina once again faces high, persistent, and volatile inflation. With a looming presidential election several options, including dollarization, are being discussed to stabilize prices and put the economy on a path of sustained growth. However, because of acute institutional anomie, which makes non-contingent rules under domestic jurisdiction easily reversible, even the best-intentioned policymakers cannot generate sufficient credibility. The country remains trapped in stop-go cycle of reforms that accelerates its economic decline. The root of the problem can be traced back to populism, which heightened time-inconsistency and then destroyed the formal and informal mechanisms that could have helped moderate it. With acute institutional anomie, an effective commitment device requires surrendering discretion in monetary affairs to a foreign jurisdiction. The paper explores whether dollarization can fulfill such role given Argentina's history of reform reversal and current circumstances. The evidence suggests that, in the long-run, the strongest insurance against reversal is the support of the electorate, but in the short-run, institutional design plays a critical role.
Keywords: B17; B2; B22; B27; B3; F31; F32; O24; 330; Foreign Exchange Rate Regimes; Dollarization; Monetary Policy; Time Inconsistency; Anomie; Argentina